Infectious Disease Complications in Cancer Patients - Seo, Susan K. (Crit Care Clin, 2020)
Critically ill cancer patients requiring intensive care unit (ICU) stay are vulnerable to infection due to a variety of factors, including local tumor effects, complex cancer treatments, disruption of physical barriers, neutropenia, humoral and/or cellular dysfunction, asplenia, and presence of foreign devices. Recognizing that cancer patients can have multiple immune defects concurrently is critical since it will affect diagnostic and therapeutic decision-making. This chapter describes common infectious complications that critical care teams may encounter while caring for cancer patients.